Inhalable chitosan microparticles for simultaneous delivery of isoniazid and rifabutin in lung tuberculosis treatment. (3rd August 2019) - Cunha, Ludmylla; Rodrigues, Susana; Rosa da Costa, Ana M.; Faleiro, Leonor; Buttini, Francesca; Grenha, Ana
Abstract: The direct delivery of antibiotics to the lung has been considered an effective approach to treat pulmonary tuberculosis, which represents approximately 80% of total cases. In this sense, this work aimed at producing inhalable chitosan microparticles simultaneously associating isoniazid and rifabutin, for an application in pulmonary tuberculosis therapy. Spray-dried chitosan microparticles were obtained with adequate flow properties for deep lung delivery (aerodynamic diameter of 4 µm) and high drug association efficiencies (93% for isoniazid and 99% for rifabutin). The highest concentration of microparticles that was tested (1 mg/mL) decreased the viability of macrophage-differentiated THP-1 cells to around 60% after 24 h exposure, although no deleterious effect was observed in human alveolar epithelial (A549) cells. The release of LDH was, however, increased in both cells. Chitosan microparticles further evidenced capacity to activate macrophage-like cells, inducing cytokine secretion well above basal levels. Moreover, the propensity of macrophages to internalize microparticles was demonstrated, with uptake levels over 90%. Chitosan microparticles also inhibited bacterial growth by 96%, demonstrating that the microencapsulation preserved drug antibacterial activity in vitro. Overall, the obtained data suggest the potential of chitosan microparticles for inhalable lung tuberculosis therapy.